Interpreting quantum theories the art of the possible - Ruetsche, Laura (Oxford : Oxford University Press, 2011)
Philosophers of quantum mechanics have generally addressed exceedingly simple systems. Laura Ruetsche offers a study of the interpretation of more complicated systems, and an underexplored family of physical theories, such as quantum field theory and quantum statistical mechanics, shows why they repay philosophical attention.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Quantum theory -- Philosophy